2019
DOI: 10.15406/unoaj.2019.07.00258
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and prostate cancer: a systematic review

Abstract: Exercise could also result to reductions in obesity and oxidative stress and a modulation of immune responses in prostate cancer patients. 15 Exercise causes reductions in circulating levels of testosterone and insulin-like growth factors 16,17 therefore reducing the development and spread of neoplastic cells. Apart from exercise, testosterone levels are controlled by diet, 18 and this may contribute to variances in exercise response among various populations. 19 The aim of this review was to evaluate the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…There is evidence that planned exercise is a possible adjunctive strategy linked to significant improvements in outcomes related to debilitating symptoms of cancer, including prostate cancer, where there is improvement in exercise tolerance, physical functioning during conventional adjuvant therapy, thus resulting in improved quality of life [8].…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence that planned exercise is a possible adjunctive strategy linked to significant improvements in outcomes related to debilitating symptoms of cancer, including prostate cancer, where there is improvement in exercise tolerance, physical functioning during conventional adjuvant therapy, thus resulting in improved quality of life [8].…”
Section: Resultsmentioning
confidence: 99%
“…It also lessens circulating levels of inflammation, insulin and unfavourable sex hormones, thereby preventing PCa progression. 58 As seen on Table 3, the majority of the participants engaged in weekly physical activities of ≤ 5 h across the life phases. Less than 2 h walk per week was associated with T3 or T4 tumour stage (p = 0.019).…”
Section: Prostate Cancer Stage and Grade At Diagnosis And Association...mentioning
confidence: 99%
“…Effect of physical activity on prostate cancer in overweight/obese men the evidence for an association between PA/exercise and Pca incidence shows changing effect (Liu et al, 2000;Littman, Kristal, White, 2006;Lynch, 2010;Liu et al, 2011;grotta et al, 2015;Benke, Leitzmann, Behrens, Schmid, 2018;McTiernan et al, 2018;Berger et al, 2019;Deb, Emmanuel, Emara, 2019) and is classified as limited suggestive (Wcrf/AIcr, 2018, McTiernan et al, 2019. Physical activity has not been consistently associated with Pca incidence, some studies have suggested an association between higher PA and decreased risk of PCa incidence, whereas other studies did not find such association.…”
Section: Effect Of Physical Activity/exercise On Body Weight and Body...mentioning
confidence: 99%
“…Physical activity has not been consistently associated with Pca incidence, some studies have suggested an association between higher PA and decreased risk of PCa incidence, whereas other studies did not find such association. For example, Deb et al (2019) reviewed studies from 1980 to 2018 on the relationship between PA and Pca incidence risk. the authors found increased risk or no effect of occupational PA in 10 studies, positive trend decreasing cancer risk with increasing level of PA in 4 studies, and a statistically significant decreased risk in the more active men (based on 10 studies).…”
Section: Effect Of Physical Activity/exercise On Body Weight and Body...mentioning
confidence: 99%